The Effectiveness of Mosquito Breeding Site Eradication and Role of Wiggler Controller toward Countermeasure Effort of Dengue Hemorrhagic Fever in Klaten, Central Java - Riska Chandra Pradana; Ruben Dharmawan; Endang Sutisna Sulaeman (Masters Program in Public Health, 2016)
Background: Countermeasure of Dengue Hemorrhagic Fever (DHF) is more prioritizing in preventive activities such as implementing mosquito breeding site eradication or PSN through 3M plus by involving the society and facilitating the establishment of wiggler controllers or Jumantik. Role of wiggler controllers is very important especially in initial vigilance system moreover in the outbreaks of DHF because of their function in monitoring the wigglers’ position and hampering the initial development of DHF transmitter vector. The activeness of wiggler controllers in monitoring their environment is expected to decrease the number of DHF cases. This study was aimed to investigate analyzing the effectiveness of mosquito breeding site eradication and the roles of wiggler controllers or Jumantik in prevention and countermeasure efforts of DHF.Subject and Methods: This was a qualitative study with case design. This was conducted in Juwiring, Ngawen, North Klaten community health center in Klaten, Central Java were selected by Purposive Sampling. The data was collected with observation, document analysis, and in-depth interview. The data validity included a triangulation, methodological triangulation, and theory triangulation. The data was analyzed with data collection, data reduction, data presentation, and drawing the conclusion were included in the data analysis of this research.Results: Several obstacle factors were people’s behavior which was not routinely doing the eradication of mosquito breeding site or PSN, lack of knowledge about PSN, lack of health workers especially in PSN program and the role of public figure was not maximum yet. Those could be seen from the outcome of PSN program which was divided by the output of PSN. Morbidity rate of DHF and mortality rate of DHF in Klaten District were still high and did not achieve the national target yet. Then, people’s knowledge about PSN program was quite good, people’s behavior was also good especially to the implementation of PSN program although some of them behaved poorly, their reliance and trust were good especially to the implementation of PSN program, then, there were no contradictions between society values and PSN Program. Health facilities and infrastructures were adequate to perform individual health effort in promotive, preventive, curative, or rehabilitative which were done by the government, regency government, or the society especially to encourage the implementation of PSN program. Amount of health officers for the implementation of PSN Program was not ideal yet, especially for Epidemiology officers and Health Promotion officers. Public and government supports were quite good in the implementation of PSN Program. Attitude and behavior of public figures, religious leaders, and also health officers were quite good. Although some of public figures did not give their full support. Government policy in encouraging the implementation of PSN Program itself was quite good. That was proven by publishing Region Regulation No. 03 of 2010 and Regent Regulation No. 05 of 2013 about prevention and disease control from animal sources, but its implementations were not maximum and binding yet. The role of wiggler controllers in decreasing the rate of DHF cases could be optimized by specific commitment from the policy makers, started from the highest to the lowest in order to build better initial vigilance system. Operational fund for the wiggler controllers (Jumantik) in Klaten District was not ideal yet, so, commonly they spent their own money for the operational fund when they did their job.Conclusion: The effectiveness of PSN Program in Klaten District to overcome DHF was effective enough. The role of predisposition factor toward mosquito breeding site eradication or PSN in order to overcome DHF in Klaten District was became the booster of the implementation of mosquito breeding site eradication program (PSN). Enabling Factors are enormously important in implementing the PSN Program in the public. The encourage factor on PSN program was not maximum yet, especially in the implementation of Region Regulations and Regent Regulations particularly about Prevention and Disease Control from Animal Source. The roles of wiggler controllers in the countermeasure of DHF in Klaten District was very important especially for the initial vigilance of DHF because its functions were used to monitor their existences and also hamper the initial development of DHF transmitter vectorKey words: mosquito breeding site eradication, DHF, the role of wiggler controllersCorrespondence : Riska Chandra Pradana. Dr. R Soeprapto Cepu Hospital. Email: pradanachan@gmail.comJournal of Epidemiology and Public Health (2016), 1(1): 37-48https://doi.org/10.26911/jepublichealth.2016.01.01.05